ASSESSMENT OF POSSIBLE INDIRECT RISK OF NATURALLY OCCURING MERCURY AND CADMIUM THROUGH Mugil Sp. AND Geloina sp. CONSUMPTION IN SEGARA ANAKAN ESTUARINE ECOSYSTEM - Sri Noegrohati (Universitas Gadjah Mada, 2005)
Estuarine ecosystem of Segara Anakan is located in south coast of Central Java, shielded from Indian Ocean by Nusakambangan island. The ecosystem of Segara Anakan estuary, Central Java, Indonesia, is influenced by fresh water inflow from Citanduy river basin and Indian sea water mostly by tidal actions through the western opening. The runoff materials continuously entering Segara Anakan from Citanduy catchment area, which geologically consist of weathering products of quarternary volcanic rocks from Galunggung mountain, West Java. Therefore various natural heavy metal contaminants are bound to the estuarine sediments, redistributed and accumulated within the ecosystem. In the present work, the effects of environmental stresses to mercury and cadmium abiotic distribution, and their availability to biotic ecosystems were studied, and consumers indirect risk assesment was carried out. In the laboratory scale studies on the distribution of mercury and cadmium in an estuarine simulation of water-field sediment, it was observed that the metal distribution coefficient decreases as the salinity and the acidity of the medium increases. Monitoring results confirmed that the highest levels of Hg and Cd in water and sediment samples were obtained in dry season. Consequently, the highest levels of Hg and Cd in biotic ecosystem, represented by Mugil sp. and Geloina sp., also obtained in dry season. The body burden of Hg in people of Segara Anakan villages, as indicated by the levels in hair and mother milk samples, taken at the end of the study (dry season 2004), were relatively low, but the levels of Cd in mother milk samples were significantly higher than that of control samples of Jogyakarta (P = 0.05). Consequently, the risk quotient for babies were exceeding the FAO/WHO PTWI. Based on the risk assessment carried out for babies and adults, at the present time it is advisable to consume Mugil sp. and Geloina sp., taken in wet season only and not in dry season.